Significance of plant E3 ubiquitin ligases in NPK homeostasis: A review - Sanjib Patra; Arunava Mandal (Plant Stress, 2023)
Growth and development of a plant depends entirely on the availability of macronutrients. In nature macronutrients are not the limited elements, indeed, it is adequately present in soil due to its rapid recycling mechanism. But in modern agricultural system NPK are three serious limited components and therefore added as fertilizers. NPK are precious macronutrients that are involved in protein, chlorophyll, nucleic acid and membrane phospholipid biosynthesis. Plants have evolved several metabolic and physiological mechanisms to avoid NPK deficient condition. The post translational modification like ubiquitination act as a crucial factor for providing tolerance towards nutrient stress condition. The ubiquitination phenomenon involves, five crucial component namely ubiquitin (Ub), E1, E2, E3 and the 26 s proteasome. The E3 ubiquitin ligase is a leading part of UPS that play key role to recognize the target protein and promotes the transfer of ubiquitin molecule to the target protein. Few reports demonstrate the hidden connection between ubiquitin and their target and how they can lead plant to deal with NPK homeostasis. In these review we summarizes and concentrate on ubiquitination process and significance of plant E3 ubiquitin ligase during NPK deficiency condition.